2007
DOI: 10.1152/ajplung.00449.2006
|View full text |Cite
|
Sign up to set email alerts
|

Lung antioxidant enzymes are regulated by development and increased pulmonary blood flow

Abstract: SM. Lung antioxidant enzymes are regulated by development and increased pulmonary blood flow. Am J Physiol Lung Cell Mol Physiol 293: L960-L971, 2007. First published July 13, 2007; doi:10.1152/ajplung.00449.2006.-Increasing data suggest that oxidative stress, due to an increased production of reactive oxygen species and/or a decrease in antioxidants, is involved in the pathophysiology of pulmonary hypertension. Several antioxidant systems regulate the presence of oxidant species in vivo, and of primary inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…However, cellular levels of H 2 O 2 can be increased in the face of constant superoxide generation if the levels of scavenging are attenuated. Indeed, we have previously shown that increases in shear stress in vivo can result in decreased catalase expression and activity (44). Furthermore, it has also been previously reported that laminar shear stress (10 dyn/cm 2 , 16 h) decreases catalase activity as well as the activities of other phase 2 detoxifying enzymes (glutathione reductase, glutathione peroxidase, and glutathione S-transferase) in human umbilical vein ECs (20).…”
Section: Discussionmentioning
confidence: 69%
“…However, cellular levels of H 2 O 2 can be increased in the face of constant superoxide generation if the levels of scavenging are attenuated. Indeed, we have previously shown that increases in shear stress in vivo can result in decreased catalase expression and activity (44). Furthermore, it has also been previously reported that laminar shear stress (10 dyn/cm 2 , 16 h) decreases catalase activity as well as the activities of other phase 2 detoxifying enzymes (glutathione reductase, glutathione peroxidase, and glutathione S-transferase) in human umbilical vein ECs (20).…”
Section: Discussionmentioning
confidence: 69%
“…This suggests that the antioxidant capacity of the cells may also affect the eNOS expression. Recently, we have reported that, in the lamb, lung antioxidant enzymes catalase, SOD1, and SOD2 are regulated both by development and by increased pulmonary blood flow (39). Additional research is therefore warranted to characterize further the complex redox regulation of eNOS expression in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Archer et al described an epigenetic attenuation of Sod2 in pulmonary arterial hypertension (3). In contrast, Sod2 expression was up-regulated over time in a lamb model of increased postnatal pulmonary blood flow, secondary to in utero aortopulmonary graft placement (77). In human IPAH, Fijalkowska et al observed a decreased Sod2 expression, but this decrease was shown in endothelial cells only (27).…”
mentioning
confidence: 94%